Quality assessment and deviation analysis of three-dimensional geometrical characterization of a metal pipeline by pulse-echo ultrasonic and laser scanning techniques. (October 2019) - Marció, Bruno Silva; Nienheysen, Philipp; Habor, Daniel; Flesch, Rodolfo C.C.
Highlights: The inner surface of a metal specimen with known flaws was inspected. Ultrasonic presented errors with smaller magnitude than laser scanning technique. The presence of artifacts near the defect edges affected laser technique performance. Ultrasonic technique demanded more time for inspection than laser scanning technique. Abstract: Although ultrasonic-based techniques are the most widely used ones for the assessment of pipeline integrity they have some limitations, and alternative methods show potential to overcome them, such as laser scanning techniques. This paper presents the results of an experimental evaluation of pulse-echo ultrasonic and laser scanning techniques for pipeline inspection using a metal specimen which represents a damaged pipeline. Both techniques were able to detect all the defects on the inner surface of the specimen, but the defect geometry was important to define the accuracy of each technique. For almost all the evaluated defects, the differences between the reference and the three-dimensional representations created from the experimental data showed that the ultrasonic technique presented errors with magnitude around 0.2 mm, which is in general half the error observed for the laser scanning technique. However, ultrasonic technique demanded 8 h for specimen inspection, while laser technique required only 10 min.